The Correlation between listening skill and speaking skill student of Arabic language education department - Fadhil BN (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
The main problem is the listening skills, Speaking skills, and correlation between listening skills and speaking skills in fifth grade students of the Arabic Language Education Department, Tarbiyah faculty and teacher training at Imam Bonjol University Padang. The research method used is a descriptive-correlation method, and data are presented in the form of numbers and analyzed by statistical methods, The method of data collection in this study was to use an audio test and an oral test, and the research sample consisted of 25 students, all of them is fifth grade students of Department of Arabic Language Education Faculty of Tarbiyah and Teacher Training Imam Bonjol University Padang. This study reached the results, as found from the results of the fifth grade, and the highest result for listening skills was eighty-eight and the lowest was seventy-three. And The results for speaking skills the highest was eighty-six and the lowest was seventy, There is a strong correlation between listening skills and speaking skills among fifth grade students in Arabic language education department. This correlation is indicated by the results achieved by students of 1% = 0.505 and 5% = 0.369, and the results of the correlation between listening skills and speaking skills are 0.574 This shows a strong correlation